Personality science, resilience, and posttraumatic growth - Jayawickreme, Eranda; Forgeard, Marie, J.C.; Blackie, Laura E.R. (Cambridge University Press, 2015)
PASTOR represents an innovative development in the study of resilience. This commentary highlights how PASTOR can help both clarify critical questions in and benefit from engaging with new research in personality science on behavioral flexibility across situations in addition to stability over time, and also clarify the relationship between resilience and posttraumatic growth.